CuS-Bridged MXene-Based Photoresponsive Phase Change Materials Enabling Thermoelectric Cogeneration and Microwave Absorption - Feng, Yuhao; Zhao, Jindi; Chen, Keke; Li, Yang; Liu, Jiao; Yu, Huitao; Qin, Mulin; Jia, Kaihang; Han, Haiwei; Shen, Zhenghui; Ma, Mingliang; Chen, Xiao (Nano-Micro Letters, 2026)
Designing multifunctional materials integrating efficient photoresponsive thermoelectric cogeneration with microwave absorption remains challenging for clean solar energy utilization and electromagnetic interference mitigation. Herein, this study proposes an innovative design strategy combining interfacial bridging engineering and physical encapsulation to construct advanced multifunctional composite phase change materials (PCMs). A nanoparticle-bridged 3D interpenetrating phonon network is constructed via in-situ growth of CuS nanoparticles on layered MXene, creating abundant interfacial sites for polyethylene glycol (PEG) adsorption and efficient electron transport channels for electromagnetic loss. The resulting PEG-MXene@CuS composite PCMs achieve an exceptional photothermal conversion efficiency of 94.5% (100 mW cm−2), enabled by broadband absorption of MXene nanosheets and plasmonic effect of CuS nanoparticles. In photoresponsive thermoelectric cogeneration system, PEG-MXene@CuS serves as a heat source to drive thermoelectric module through the Seebeck effect, yielding a stable power output of 21.7 W m−2 (100 mW cm−2), with PEG effectively buffering thermal fluctuations. Moreover, MXene@CuS heterointerface and 3D conductive network endow PEG-MXene@CuS with superior microwave absorption, a minimum reflection loss of − 55.5 dB and an effective bandwidth of 5.27 GHz. This design concept provides important insights into designing next‑generation multifunctional PCMs with promising applications in intelligent thermal management, thermoelectric cogeneration, and electromagnetic protection. Hightlights: 1 An interfacial bridging strategy is utilized to construct a 3D interpenetrating network for accelerated phonon/electron transport. 2 The synergy of localized surface plasmon resonance effects and phase change thermal buffering enables efficient solar harvesting and stabilized thermoelectric cogeneration. 3 Enhanced interfacial polarization and optimized impedance matching significantly boost electromagnetic energy dissipation.